Design of a Web-Based Incoming Goods Information System to Support Logistics Performance at Bintang Technic - Putra Febriansyah, Ragil (Yayasan Kawanad, 2025)
This study addresses logistical inefficiencies at Bintang Technic, a technical equipment trading startup in Malang Regency, East Java, where manual recording led to delays, inaccurate stock data, and limited transparency, with 10–15 monthly distribution delays and over 15% error rates in transactions. Utilizing a Research and Development (R&D) approach, a web-based information system was developed using Laravel and MySQL to streamline incoming goods management. Through qualitative data collection via observations and interviews, the system was designed with integrated database structures, role-specific dashboards for operations (item management, requests), finance (request reviews, vendor management, POs), and managers (approvals, reports), supported by use case diagrams, DFD, and ERD. Stakeholder feedback refined the design, and Black Box Testing across 21 scenarios confirmed 100% functionality, reducing processing times from 2–3 days to under 1 day and errors from 15% to below 3%. The system enhanced transparency, decision-making, and efficiency through real-time data and automation, overcoming challenges like user resistance and infrastructure limitations via training and technical support. This solution not only meets Bintang Technic’s needs but also offers a scalable model for SMEs, with potential for integration with other business modules.